The Potential of Kalelo Yogurt as Supplementary Foods to Prevent Stunting - Pengge, Nuning Marina; Sayuningsih, Eny; Ratna Sari, Devi Eka; Hindaryani, Nurul; Mujayanto; Sariman, Sarina; Hafid, Fahmi; Taufiqurrahman (Poltekkes Kemenkes Palu, 2024)
This study aims to determine the potential of kalelo yogurt as supplementary feeding to prevent stunting. This type of research was pre-experimental with the Post-test only design method with the yogurt formula treatment. The statistical analysis used was Complete Randomized Design (CRD) 3 X 2 followed by Duncan test to see the difference in each formulation. And the organoleptic test of kalelo yogurt was processed using the Analysis Of Variant (ANOVA) test and Duncan test to see the level of difference significant at α level of 0.05. Results: The best formula of kalelo yogurt based on nutrient content was F1, which was consumed simultaneously with other foods to increase its nutritional value. While organoleptic tests showed F3 as the best product, with a rating level of (somewhat dislike-neutral). Based on the test results, the panelists still did not like kalelo yogurt very much, as it can be seen from the results of panelist evaluations ranging from somewhat dislike to neutral (4-5). This could be due to the aroma, taste and texture that were different from a solid yogurt. With increasing incubation time, microbial activity increases and the number of microbes increases, resulting in the pH of the medium decreasing. The best kalelo yogurt product from organoleptic and nutrient content was F3 and F1, respectively. The nutritional, energy and micronutrient content of the three formulas were not significantly different. To fulfill the nutritional needs of sufficient numbers requirements, pregnant women are advised to consume several times a day accompanied by other foods.